Efficacy of Putri Malu Leaf Plant (Mimosa Pudica Linn) as Hepatoprotectors on Ibuprofen Induced Hepatic Damage in White Mice (Mus Musculus) - Bagaskara, Andre; Triastuti, Nenny; Yuliyanasari, Nurma; Annisa Ayu Rezkitha, Yudith; Anas, Muhammad; Indra Alfaray, Ricky (Universitas Muhammadiyah Semarang, 2022)
Background:Putri Malu plants (Mimosa pudica linn) contain flavonoid compounds that are useful as hepatoprotectors. Putri Malu plants extract can be usefull to prevent problem such as Ibuprofen-induced hepatic damage., but study that focus on this topic remain scarce in Indonesia. Objective: To prove the extracted content of the leaves of the Putri Malu plant (Mimosa pudica linn) as a hepatoprotector of hepatic damage in mice (Mus musculus) induced by Ibuprofen. Method: This randomized post-test control group design was conducted at the Experimental Animal Laboratory, Faculty of Veterinary Medicine, Universitas Airlangga. A total of 28 mice were treated with four condition then underwent SGOT and SGPT blood laboratory tests. Results: Group P1 (placebo) had SGOT and SGPT levels averaging 23.87 mg/dl and 13.45 mg/dl, group P2 (ibuprofen dose 7 mg/KgBW) had SGOT and SGPT levels of 29.13 mg/dl and 19.10 mg/dl, group 3 (Putri Malu extract 35 mg/KgBW) had SGOT and SGPT of 24.05 mg/dl and 13.56 mg/dl, and group 4 (ibuprofen dose 7 mg/KgBW and Putri Malu extract of 35 mg/KgBW) showed SGOT and SGPT levels of 28.23 mg/dl and 18.35 mg/dl. The four groups had different mean SGOT and SGPT levels (P 0,000). Conclusion:Leaf extract of the Putri Malu plants (Mimosa pudica linn) has a chemical effect of heaptoprotector as shown by the decrease in SGOT and SGPT level.